A Qualitative Study and Improvement on UX and Usability Evaluation Questionnaire focused on Multi-touch Systems - Filho, Guilherme Eduardo Konopatzki; Valentim, Natasha Costa; Guerino, Guilherme Corredato (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Multi-touch systems have been popularizing in the last years. This kind of system needs to pass through an evaluation to ensure they reach a good quality level. The usability and User eXperience (UX) indicators are well-fitted to provide the necessary subsidy for this quality. There is a lack of technologies specifically built to evaluate the usability and UX in the multi-touch context, focusing on its specificities, such as lack of touch precision, and lack of mechanical feedback, among others. To fulfill this lack, the User eXperience and Usability Multi-touch Evaluation Questionnaire (UXUMEQ) was created. As any new technology, it needs to pass through a validation process to ensure that it fulfills its purpose. Therefore, a qualitative study was carried out, where 11 Software Engineers and Human-Computer Interaction experts evaluated UXUMEQ and participated in an interview. Their impressions were analyzed through of the first two stages of Grounded Theory method. Several suggestions led to a review and update of UXUMEQ, such as avoiding confusion regarding concepts, standardization in the format of questions, and additions of questions to evaluate specific multi-touch gestures. This study is the third step of research using an evidence-based methodology. We expect that the improvements made in UXUMEQ will support end users and other evaluators in identifying more usability and UX problems in the multi-touch context.